HUBUNGAN DANA PIHAK KETIGA TERHADAP KREDIT BANK PEMERINTAH YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2003 – 2018 - Cynthia Ayu Lestari; Ihsan Effendi; Eka Dewi Setia Tarigan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to avoid the "Third Party Fund Relationship of Government Banks listed on the Indonesia Stock Exchange for the period 2003 - 2018" which includes demand deposits, time deposits and savings against loans extended by the bank government. The sample data is 64 samples (from 2003 - 2018). By using descriptive test method, do not know test and moving average method and third party fund growth. The test results show the simultaneous influence of third parties on bank government credit. The correlation coefficient test shows that third party funds are positive and significant for credit. Meanwhile, the growth of third party funds is not stable every year.